Storytelling as Innovative Method to Improve the Recognition of Teledentistry among Adults: A Randomized Controlled Trial - Khalid Aboalshamat; Fayyad Alsharif; Bader Alsanei; Alaa Aljohani; Saad Aljabri; Rayan Salawati; Afnan Nassar (International Journal of Dentistry)
Objective. Storytelling is an educational approach that encourages learners to create imaginative conceptions and think creatively. The aim of this study was to assess the effects of storytelling on improving awareness about teledentistry among adults in Saudi Arabia. Materials and Methods. A single-blinded parallel group randomized controlled study with 88 adult participants from Saudi Arabia. Participants were randomized into an intervention group (IG) or a control group (CG). The IG received teledentistry information using a storytelling method, while the CG received a flyer containing the same information. The participants were questioned three times: P1 before the intervention, P2 immediately after the intervention, and P3 1 month later. Results. A total of 83 participants completed all study steps. No significant knowledge score differences between IG and CG at P1, P2, or P3 nor in mean differences across time points. However, significant increase from P1 to P2 (p<0.001) and P1 to P3 (p<0.001) via paired t-test; no change from P2 to P3 in IG (p = 0.99) or CG (p = 0.816). Storytelling was significantly more innovative and emotionally touching than conventional flyer. The study was registered with the number ISRCTN68587630. Conclusion. Storytelling was found to be a more innovative and emotionally impactful approach for promoting health compared to traditional flyers. Future studies should extend follow-up periods and explore diverse stories for external validation of this method.